Human Cytomegalovirus II. Lack of Relatedness to DNA of Herpes Simplex I and II, Epstein-Barr Virus, and Nonhuman Strains of Cytomegalovirus - Huang, Eng-Shang (1974)
The purified DNA of human cytomegalovirus, radiolabeled in vitro, was examined for homology to Epstein-Barr virus, herpes simplex type I and II, and simian and murine cytomegalovirus DNA by DNA-DNA reassociation kinetics analyses with the S1 enzyme differential digestion technique. Cross-matching of the DNAs showed no relatedness or less than 5% detectable homology.